Budaya Organisasi, Motivasi Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Rumah Sakit Semen Gresik - Tajuddin, Mohammad; Tumirin, Tumirin; Desembrianita, Eva (Jurnal Manajerial, 2020)
Background - Hospitals as a health service organization in order to "survive" must have a good service management system so that the impact on employee performance can meet the demands of the community’s needs. Objectives - This study aims to determine the extent of job satisfaction and employee performance at Semen Gresik Hospital which is influenced by organizational culture and work motivation.Design / Methodology / Approach - The object of this study is Semen Gresik Hospital. Sample in this study used a purposive sampling method with the provisions of respondents who worked more than 5 years while through the formula Slovin determined the number of research samples of 219 respondents. Statistical tests use path analysis.Results and Discussion - Based on the results of the analysis prove that organizational culture and motivation directly and indirectly influence employee performance and job satisfaction, the findings of organizational culture have a smaller coefficient on employee performance and job satisfaction compared to work motivation and based on analysis testing The path of organizational culture has a total value smaller than work motivation. So the results of the study concluded that organizational culture and motivation can increase job satisfaction and employee performance.Conclusion - All hypotheses this study are proven and can be accepted. Organizational Culture, work motivation has direct and indirect effects on employee performance and job satisfaction.Research Implications - It is hoped that the results of this study can contribute to knowledge and hospital management to pay attention to organizational culture and work motivation to improve employee performance and employee satisfaction at work.